Do Firms Approach the Target Working Capital Requirement? A Case of Pakistan - Shaikh, Ruqia; Memon, Pervaiz; Shaique, Muhammad; Hassan, Ehsan ul (UI Scholars Hub, 2018)
The study investigates the dynamism of working capital requirement (WCR) in non-financial firms listed on Pakistan Stock Exchange from the period of 2007 to 2013. The purpose of this research is to analyze whether firms follow the target WCR, to estimate the speed with which firms adjust towards its target WCR and to investigate the firm specific and macroeconomic determinants of WCR. Difference GMM technique is used to analyze the speed and determinants of WCR to avoid the problems of endogeniety and unobservable heterogeneity. The study gives evidence that there is an existence of target WCR in firms of Pakistan and firm require 1.6 years to completely adjust back to target WCR. The factors which are statistically significant in determination of WCR are: the level of economic activity in the country, operating cash flow, profitability, leverage, financial distress, and financing cost. The WCR is measured by net trade cycle of a firm.